Automatic anesthesia regularization system (AARS) with patient monitoring modules - Krishnakumar, S; Bethanney Janney, J; Antony Josephine Snowfy, W; Joshin Sharon, S; Vinodh Kumar, S (International Journal of Engineering and Technology, 2018)
The administration of high/low dose of anesthesia during surgery may cause lethal effect to the patient. To avoid such situation, the anesthetist administers few milliliters of anesthesia at regular intervals to the patient. To overcome such tedi-ous problems, this project aims to design an effective microcontroller based automatically operated anesthesia machine. In the proposed Automatic Anesthesia Regularization System, anesthesia level is controlled by multi-task feedback and microcontroller system, based on patient’s condition. The Automatic Anesthesia Controller designed using microcontroller aids to control anesthesia levels during the course of surgery. Mechanical syringe infusion pump is provided to deliver an-esthesia to the patient. The anesthetist can set the keypad to administer the dose of anesthesia in terms of milliliters per hour. The keypad transmits the analog signal to the microcontroller to control the required dose of anesthesia to be fed into DC motor to operate injection pump. The anesthesia was administered based on patient’s body condition and move-ment of syringe in the forward or backward direction based on the rotation of DC motor. This module will play a major role in the field of medicine and useful to the physicians during major surgery to provide the desire amount of anesthesia.